HOLOCENE FAULTS (INFERRED PALEOSEISMIC DISLOCATIONS) AND THE ASSESSMENT OF EARTHQUAKE HAZARD FOR THE KORYAK AUTONOMOUS DISTRICT, NORTHEAST RUSSIA - Leonov V.L. (My University, 2000)
Areal interpretation of air photographs was carried out for the Koryak Autonomous District (KAD) which includes the northern part of Kamchatka and the southern Koryak Highlands (ca. 240 000 km2) to locate young (Holocene) faults, fissures, and their combinations as hypothetical paleoseismic scarps (or traces of old large (M > 6.5) earthquakes). In all, 410 features were located, their abundance and density were mapped, and the variability of their strikes was analyzed. Also located were hypothetical seismogravitational features, such as landslides, rockfalls, and soil liquefaction sites. This paper is concerned with the problems related to earthquake hazard assessment for the region of study and with the location of areas differing in structure and in the number and dominant trends of paleoseismic ruptures. It is shown that the distribution of the latter is generally consistent with the disposition of major structural zones in the area.
Keywords: Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен